Retrospective Study of Seborrhoic Dermatitis Patients at the Dermatology and Venereology Outpatient Installation - Hidayati, Nurul; Irawanto, Muhammad Eko; Alia, Vrenda; Ivani, Ivani (Journal La Medihealtico, 2025)
Seborrheic dermatitis is a chronic superficial skin disorder occurs in 1-5% of the world's population with the symptom of erythematous plaque with slightly yellowish scaling and without clear border, it caused by multifactorial etiopathogenesis includes sebaceous gland secretion, Malassezia fungi colonization, and immune response. This study aims to determine the profile of seborrheic dermatitis patients in Dermatology and Venereology Outpatient Installation of Dr. Moewardi Surakarta General Hospital in January 2021 - December 2023 period. This study is a retrospective study using medical record data from seborrheic dermatitis patients who visited the Dermatology and Venereology Outpatient Installation of Dr. Moewardi Surakarta General Hospital from January 2021 to December 2023. The data collected included the number of cases, age group, gender, occupation, lesion location, and therapy options. Seborrheic dermatitis affected 76 people. Men are more likely to have seborrheic dermatitis than women; up to 43 patients (56.6%) and 30 patients (39.5%) are adults, the oldest age group with the condition. Up to 27 patients (35.5%) who suffer from this disease are private employees, 43 patients (56.6%) with comorbidities, and up to 65 patients (85.5%) frequently have lesion in their head. The most common therapy given was topical corticosteroid combined with anti-fungal in 38 patients (50.0%). In this study, the topical corticosteroids that were widely used were mometasone 0.1% cream and desoxymetasone 0.25% cream, topical antifungal that were widely used were ketoconazole 2% shampoo and ketoconazole 2% cream. Male adults are most likely to develop seborrheic dermatitis.